2020
DOI: 10.1177/0265407520961178
|View full text |Cite
|
Sign up to set email alerts
|

Approach and avoidance motives for touch are predicted by attachment and predict daily relationship well-being

Abstract: Research suggests that touch promotes relationship well-being but has failed to consider motives for touch. We assessed general (Study 1) and daily (Study 2) approach and avoidance motives for touch and tested their precursors and consequences. Controlling for relationship quality and the other motive, greater attachment avoidance predicted lower approach and greater avoidance motives for touch in general but did not predict motives in daily life. Greater attachment anxiety simultaneously predicted greater app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…For example, it is logical to predict that loving partners would use more touch in their relationships, enriching communication, and enjoying the benefits typically associated with affectionate touch. Touch, at the same time, could promote love between partners, in line with a study showing that one’s own and one’s partner’s approach motives for touch predict greater daily relationship well-being 27 . This hypothesis finds support in an older study by Dainton, Stafford and Canary 28 who showed that physical affection (including touch behaviors) performed by a romantic partner as well as satisfaction with physical affection displays were positively related with self-assessed love level.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…For example, it is logical to predict that loving partners would use more touch in their relationships, enriching communication, and enjoying the benefits typically associated with affectionate touch. Touch, at the same time, could promote love between partners, in line with a study showing that one’s own and one’s partner’s approach motives for touch predict greater daily relationship well-being 27 . This hypothesis finds support in an older study by Dainton, Stafford and Canary 28 who showed that physical affection (including touch behaviors) performed by a romantic partner as well as satisfaction with physical affection displays were positively related with self-assessed love level.…”
Section: Introductionsupporting
confidence: 70%
“…In one of a few studies focused directly on touch in romantic partnerships, relationship quality was found to be positively associated with desire for touch, while attachment avoidance was associated with lower overall desire for touch 26 . Touch was further found to be a significant mediator between attachment patterns and relationship well-being 27 . Despite these promising findings and the obvious value of touch in close interpersonal relationships, scientific knowledge on affectionate touch in romantic relationships still remains rather sparse.…”
mentioning
confidence: 89%
“…There is some indirect evidence that touch experiences covary with relationship satisfaction. People with higher relationship quality report greater desire for touch (especially intimate forms of touch), are more motivated to touch to approach positive outcomes, and are less motivated to touch to avoid negative outcomes than those with lower relationship quality (Jakubiak et al, 2021a(Jakubiak et al, , 2021b. Additionally, people with higher relationship quality report greater actual engagement in affectionate touch (Gulledge et al, 2003;Mackey et al, 2000).…”
mentioning
confidence: 99%
“…The benefits of approach motives in relationships extend to other behaviors as well. Engaging in touch from an approach orientation produces benefits in relationship quality for both relationship members (Jakubiak et al, 2021).…”
Section: Relational Agency Promotes Relationship Quality Via Approach...mentioning
confidence: 99%
“…The benefits of approach motives in relationships extend to other behaviors as well. Engaging in touch from an approach orientation produces benefits in relationship quality for both relationship members (Jakubiak et al., 2021). Given that individuals who feel agentic in their relationship may be more likely to pursue approach goals as a means to desired relationship outcomes, they are more likely to engage in beneficial behaviors that promote greater relationship quality both for themselves and their partner.…”
Section: The Power Of Wills Ways and Wishes: A Proposed Model Of Rela...mentioning
confidence: 99%